AN ANALYSIS OF THE STUDENTS’ PROBLEMS IN WRITING DESCRIPTIVE TEXT IN ELEVENTH GRADE AT MA MADINATUL KHAIRAAT BUNTUNA - Jaya, Jaya; Widiawati, Widiawati (Jurnal Madako Education, 2022)
The objective of this research was to find out the problems of students in writing descriptive text ineleventh grade at MA Madinatul Khairaat Buntuna. The method used qualitative research that using interview asdata collection instrument. The participants were 8 students in eleventh grade. The results showed that based onthe theory Nurgiantoro (2001) there were several problems faced by the students when writing descriptive textthey were vocabulary, grammatical mistake, and organization idea. The data collection analyzed by datareduction, data display, and conclusion/drawing verification. The problem faced in eleventh grade at MAMadinatul Khairaat in writing descriptive text was vocabulary.This indicator was most dominant problem thatfaced of students because the students had less vocabulary and determined the right word so they had problem towrite a text. Then, the problem in writing was grammar. They confused about the tenses and arranged the wordinto the sentence. The last, the problem in writing was organization idea. They confused in determine main ideabecause it might known main problems in sentence. And also they had problem in determine a theme, indetermine a theme it might look the content of writing so it could be easy to determine a theme.